The Effect of 0.05D Interval Precise Refraction on Small-Incision Lenticule Extraction Surgery: A Retrospective Study with Short-Term Follow-Up [Corrigendum] - Li J; Zhen J; Xie K; Yao K; Liu Z; Li X (Clinical Optometry)
Li J, Zhen J, Xie K, Yao K, Liu Z, Li X. Clin Optom. 2024:16:341–348. Our authors have advised that the institution name in the first sentence of the “Methods” section on page 342 should read from “This retrospective study comprised patients who had a preoperative examination, SMILE surgery and postoperative follow-up at the Department of Ophthalmology, Peking University Third Hospital and Beijing Meiermu Hospital between February 2022 and July 2022” to “This retrospective study comprised patients who had a preoperative examination, SMILE surgery and postoperative follow-up at the Department of Ophthalmology, Beijing Meiermu Hospital between February 2022 and July 2022”. The authors apologize for this error.